PERAN KATEGORI PRODUK SEBAGAI PEMODERASI CITRA NEGARA ASAL PADA EKUITAS MEREK - Endah Pri Ariningsih; Titin Ekowati; Murry Harmawan Saputra (Jurnal Bisnis dan Ekonomi, 2016)
Brand is very important for marketers as the identity for the product to be marketed in order to be distinguished from other products. Moreover, the current competition for the market not only occur between companies locally or nationally but already global as well. Country of origin is often listed together with the provision that the brand is expected to improve the equity of the brand. However, information about the country of origin is not always going to be able to increase brand equity. Still happens practically and theoretically gab about the influence of the country of origin on brand equity. Specify the country of origin was able to reduce the brand equity. The absence of studies to determine whether or not to inform the country of origin, especially for Indonesian products in order to compete in the era of globalization makes this study important. This research was conducted in order to determine consumer preference for a particular brand of product categories are associated strongly with the state of Indonesia (batik) and and is not associated strongly with Indonesia (lap top). So it can be used as a reference for marketers Indonesia to determine whether or not to inform important country of origin for their products. Research will be carried out by a questionnaire survey as a data collector. The sampling technique used purposive sampling by taking 150x2 respondents. Analysis of data to determine the moderating role of product categories on the influence of the image of the country of origin of brand equity to do with the sub-group analysis using the chow test. Keywords: origin image, brand equity, moderation, chow test